READINESS OF EARLY CHILDHOOD EDUCATION TEACHERS TO ATTEND TRAINING THROUGH DISTANCE LEARNING - Cresensia Dina Candra Kumala Dewi (Widya Mandala Surabaya Catholic University, 2021)
Research related to distance learning for students has been widely carried out, contrary to research related to teachers. The lack of opportunities and facilities for early childhood education teachers to develop their competencies is the background for the theme of this research. This article will be focused on explaining the readiness of Early Childhood Education teachers to face training conducted through distance learning. This research was conducted through a survey method by sending questionnaires to 409 participants. Participants are teachers or assistants from SPS, Playgroups and Kindergartens. The results of this study indicate that most of the participants are interested in participating in distance learning. This shows the high motivation of the participants to improve competence through distance learning. Various obstacles that may be faced cause participants to have difficulty accessing distance learning.